Improving ESP Writing Class Learning Outcomes Among Medical University Undergraduates: How Do Emotions Impact? - Hu, Nan; Chen, Min (Frontiers in Psychology, 2022)
As English plays a significant role in most professions, improving the English for Specific Purpose (ESP) writing competence allows individuals to participate in the global professional community, which makes ESP writing important for research. However, research on ESP writing is reported to be insufficient, and how factors such as emotions affect ESP writing is rarely and marginally studied. Therefore, the current study is aimed at investigating how induced emotions influence the learning outcome in ESP writing classes with emphasis on a particular rhetorical choice among medical university undergraduates. Sixty-three medical university undergraduates were recruited. After the emotional inducement, they were taught with materials selected and adopted from the BioCauses corpus and with an explicitly inductive teaching approach. Results revealed that positive emotions positively correlated with better learning outcomes, whilst negative emotions hindered participants in their learning. The results shed light on the impact of emotional states on ESP/medical research article (MRA) writing, learning and teaching. Further study implications were provided accordingly.